Integrated Effects of Water and Nitrogen Coupling on Eggplant Productivity, Fruit Quality, and Resource Use Efficiency in a Cold and Arid Environment - Jie Li; Hengjia Zhang; Chenli Zhou; Anguo Teng; Lian Lei; Yuchun Ba; Jiandong Yu; Fuqiang Li (Plants)
In order to explore the water and fertilizer requirements of eggplants in the western oasis of the river, the experiment was conducted in Minle County of Gansu Province in 2022 and 2023 under three water stress gradients and three nitrogen application levels: (1) moderate water stress (W1, 50–60% in field water capacity [FC]), mild water stress (W2, 60–70% in FC), and full irrigation (W3, 70–80% in FC); (2) low nitrogen (N1, 215 kg·ha−1), medium nitrogen (N2, 270 kg·ha−1), and high nitrogen (N3, 325 kg·ha−1). Moderate and mild water stress were applied during eggplant flowering and fruiting while full irrigation was provided during the other growth stages; a control class (CK) was established with full irrigation throughout the whole plant growth without nitrogen application. This study investigated the effects of water-saving and nitrogen reduction on the yield, quality, and water-nitrogen use efficiency of eggplants in a cold and arid environment in the Hexi Oasis irrigation area of China. Using the EWM-TOPSIS model, we evaluated different water-nitrogen treatments and determined the optimal irrigation-nitrogen application model for eggplants in this region. The results showed that the W2N2 treatment had the highest yield, which was not significantly (p > 0.05) different from the W3N2 treatment while significantly (p < 0.05) 35.06% higher than CK in 2022 and 36.91% higher in 2023. In the W2N2 treatment, the transverse diameter of eggplants, as well as the contents of soluble protein, soluble sugar, soluble solids, and vitamin C, were all the highest. The W2N2 treatment had the maximum water use efficiency and irrigation water use efficiency, which were significantly higher than other water and nitrogen application treatments and CK by 14.79–42.51% in 2022 and 8.79–44.88% in 2023, and 15.86–45.55% in 2022 and 4.68–40.22% in 2023, respectively. By employing the EWM-TOPSIS model for comprehensive evaluation, the results indicated that mild water deficit (60–70% in FC) and moderate nitrogen application (270 kg·ha−1) at flowering and fruiting of eggplants was the optimal water and nitrogen application mode under mulched drip irrigation in the Hexi region of northwest China. The results will provide some theoretical basis for water-saving, productive, high-quality, and high-efficiency cultivation of eggplant in cold and arid environments.